DEVELOPMENT OF GOLD NANOSPIKE (AUNS) MODIFIED SCREEN-PRINTED CARBON ELECTRODE (SPCE) ENZYMATIC GLUCOSE BIOSENSOR - Majidah, Salma
Integration of gold nanoparticles on electrochemical biosensor electrode has been widely carried out to improve the performance of biosensors. Gold nanospike (AuNS) as one of the gold nanoparticle morphologies, can be integrated to biosensors through electrodeposition and has potential to immobilized bioreceptor on biosensors using self-assembled monolayer (SAM). One of the bioreceptors that has been generally immobilized on gold nanoparticles is the enzyme glucose oxidase which is used as a glucose enzymatic biosensor. Glucose biosensor known as one of the gold standards for monitoring blood glucose level for diabetes mellitus patient. The fluctuation of blood glucose level throughout the day urges the patient to have a continuous and point-of-care testing. This final project examines the potential of AuNS-deposited Screen-Printed Carbon Electrode on immobilizing glucose oxidase (GOx) enzyme using L-cysteine SAM as glucose enzymatic biosensor for diabetes mellitus patient point-of care blood glucose measurement. The developed biosensor has electrochemical surface area (ECSA) for AuNS-deposited SPCE of 0,713 cm2